Before He Feels (A Mackenzie White Mystery-Book 6) - Blake, Pierce (Lukeman Literary, 2017)
From Blake Pierce, bestselling author of ONCE GONE (a #1 bestseller with over 900 five star reviews), comes book #6 in the heart-pounding Mackenzie White mystery series. In BEFORE HE FEELS (A Mackenzie White Mystery-Book 6), FBI special agent Mackenzie White is stunned to be assigned a case with victims matching no profile she has ever seen: shockingly, all of the victims are blind. Does this mean that the killer himself is blind, too? Plunged into the subculture of the blind, Mackenzie struggles to understand, finding herself out of her element as she crisscrosses the state, racing from group homes to private houses, interviewing caretakers, librarians, experts and psychologists. And yet, despite the best minds in the country, Mackenzie seems unable to prevent the spree of killings. Has she finally met her match? A dark psychological thriller with heart-pounding suspense, BEFORE HE FEELS is book #6 in a riveting new series-with a beloved new character-that will leave you turning pages late into the night. Also available by Blake Pierce is ONCE GONE (A Riley Paige mystery-Book #1), a #1 bestseller with over 900 five star reviews
Keywords: Krimi, detektivky